Unload Pull-out Test of Full-length Grouted Bolts in Slope Reconstruction and Expansion - Jiang Guan; Feng Zhongju; Ruixin Zhao; Zhangzhengxu Zhangzhengxu; Junqiang Wen (Journal of Engineering and Technological Sciences, 2021)
The Unloading Pull-out Test Method (UPTM) is proposed to evaluate the residual stress of existing anchorage systems and explore the actual stable state of the slope before excavation. A series of destructive pull-out tests are applied to detect the working state of the existing rock bolts. The working load and ultimate load of the existing bolts are determined by field test measurement of the P-S curve. The experimental result showed that a displacement increment of the bolts was present in the elastic stage, the elastoplastic stage, the slip stage, and the debonding stage. The working load and the ultimate load were in the elastoplastic stage and the debonding stage respectively. The working load of the bolts is closely related to the sliding deformation. The ultimate load of the bolts, however, is only related to the design parameters, slope lithology and other factors. After 20 years of natural forces acting on the bolts in the slope, their ultimate bearing capacity had a stress loss of 24.0% ~ 32.0%.